The role of the media in escalating social tension in the USA - Kaverina Oksana Anatolievna; Novosyolova Margarita Valerievna (SHS Web of Conferences, 2022)
The media are considered to be a pivotal source of creating and reflecting various processes in modern societies. The media’s role in escalating social tension in the USA is essential and will be examined in detail in the article. The work focuses on the language used in the media to create social tension, the phenomenon, caused by worried feelings, no trust, stress, hostility, unfriendliness, not sharing common needs or interests, anxiety, violence, and conflict. The pandemic of COVID-19 has led to inequality of views in terms of health and life-activities and has triggered off a wave of anxiety, stress and other manifestations of tension in different social spheres. The analysis of the mass media, namely publicist articles, blogs, forums, and posts in social networks, allows seeing people’s discontent about the current realities in medicine, education, ecology, and politics. People’s feelings of discontent and stress can be generally conceptualized as social tension.